2011
DOI: 10.1002/adma.201103316
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of Streptavidin Hubs for Molecular Materials

Abstract: A new strategy is reported for creating protein-based nanomaterials by genetically fusing large polypeptides to monomeric streptavidin and exploiting the propensity of streptavidin monomers(SM) to self-assemble into stable tetramers. We have characterized the mechanical properties of streptavidin-linked structures and measured, for the first time, the mechanical strength of streptavidin tetramers themselves. Using streptavidin tetramers as molecular hubs offers a unique opportunity to create a variety of well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 55 publications
5
56
0
Order By: Relevance
“…This is in agreement with former SMFS studies on the disruption of the SA dimer interface, which was found to occur at ∼100 pN (ref. 37). If high forces need to be probed, as in our exemplary GFP-unfolding experiment, monoST is a superior choice to conventional tetraST.…”
Section: Dynamic Smfs Of the Sii:monost Interactionmentioning
confidence: 99%
“…This is in agreement with former SMFS studies on the disruption of the SA dimer interface, which was found to occur at ∼100 pN (ref. 37). If high forces need to be probed, as in our exemplary GFP-unfolding experiment, monoST is a superior choice to conventional tetraST.…”
Section: Dynamic Smfs Of the Sii:monost Interactionmentioning
confidence: 99%
“…We hypothesize that high rupture forces, < F rupture-high >, are measured when Strep -tag ligands are removed from monomers belonging to one Strep -Tactin dimer and low rupture forces, < F rupture-low >, are measured when Strep -tag ligands are bound to two different dimers within the same Strep -Tactin tetramer (For details, see Supporting Information). Based on our recent study of streptavidin tetramers, [21] it is also possible that some of the rupture forces measured here may actually represent the forced separation of Strep -Tactin dimers from each other and not unbinding Strep -tag ligands. This hypothesis will be further tested by connecting our force probes directly to Strep -Tactin monomers (at the DNA level) and measuring the mechanical strength of the association of Strep -Tactin monomers within tetramers.…”
mentioning
confidence: 97%
“…When probing molecular complexes with higher affinities that will likely rupture at greater forces exceeding the unfolding force of I27, the presence of both mechanically weak and strong reference modules will be advantageous. [21] …”
mentioning
confidence: 99%
“…Indeed, the structure of streptavidin can be disrupted thermally, (62) or by mechanical stress. (27) An atomic force microscope (AFM) applying a stretching force of 100 pN at the pulling speed of 500 nm/s consistently ruptures the 4 hydrogen bonds binding the two dimers of streptavidin together. (63) Similarly, a recent theoretical study modeled the effects of a nanopore's electric field on streptavidin and found potential changes in streptavidin's secondary structure under certain pulling conditions at 2 V through a 10-nm diameter hour-glass-shaped nanopore in 1 M KCl.…”
Section: Monovalent Streptavidinmentioning
confidence: 99%